Cold hours decrease as a result of climate change in Mexico - Medina-García, Guillermo; Grageda-Grageda, José; Ruiz-Corral, José Ariel; Casas-Flores, José Israel; Rodríguez-Moreno, Víctor Manuel; de la Mora-Orozco, Celia (Revista Mexicana de Ciencias Agrícolas, 2019)
In Mexico, deciduous fruit trees are grown in the center and north of the country where the temperature, at the end of autumn and during winter, is low enough for defoliation of trees to occur and lethargy occur during winter. Global warming, as an effect of climate change, has the potential to reduce the cold available in the winter and affect the production of deciduous fruit trees. The objective of this work was to know the effect of climate change, on the accumulation of cold hours in the winter period. A historical analysis was carried out on the variation of the number of cold hours (HF) and a similar analysis in the climatic scenarios 2030, 2050 and 2070 in the 4.5 and 8.5 CPR. Both the historical analysis and the scenarios were the effects of climate change, which will be unfavorable for the cultivation of fruit trees with a temperate climate. Global warming will cause a decrease in the surface with accumulation of 600 to 800 HF of 11.7, 25.8 and 33% in climatic scenarios 2030, 2050 and 2070 of 4.5 CPR, respectively and up to 99.5% of the surface with accumulation of 800 to 900 HF in the 2070 climate of 8.5 CPR. On the other hand, the area with little accumulation of HF (50 to 200) will increase 11.5, 29.3 and 36.4% in the 2030, 2050 and 2070 climatic scenarios of the 4.5 CPR, respectively. The cultivation of deciduous fruit trees in the future will be limited by the decrease in HF, mainly in areas with greater accumulation of cold, in the same way can be affected the crops of the autumn-winter cycle such as cereals.